Synthesis of Schiff Bases via Environmentally Benign and Energy-Efficient Greener Methodologies - Arshi Naqvi; Mohd. Shahnawaaz; Arikatla V. Rao; Daya S. Seth; Nawal K. Sharma (E-Journal of Chemistry)
Non classical methods (water based reaction, microwave and grindstone chemistry) were used for the preparation of Schiff bases from 3-chloro-4-fluoro aniline and several benzaldehydes. The key raw materials were allowed to react in water, under microwave irradiation and grindstone. These methodologies constitute an energy-efficient and environmentally benign greener chemistry version of the classical condensation reactions for Schiff bases formation.